Kebijakan Strategi Penguatan Moderasi Beragama Perspektif Kurikulum Merdeka Belajar di Madrasah - Syaiful Rizal; Achmad Farid; Zulfiatul Khoiroh (Biro Perencanaan Kementerian Agama, 2023)
The threat of radicalism in schools is very frightening, so it is necessary to prevent it from an early age, starting at the elementary school level (madrasah ibtidaiyah). This study is a literature review. The results of this study indicate that the management strategy for promoting religious moderation in the Free Learning program (Merdeka Belajar) at Madrasah Ibtidaiyah (MI) must be addressed appropriately: 1) planning, ie. planning with collaborative moderation values, as well as selection of documents under the curriculum, 2) implementation, namely, the application of moderation values ​​documented in the curriculum education module, 3) control, namely, having to consider the suitability of implementing religious facilities in the curriculum, and 4) assessment, so it can run well in accordance with the learning objectives and desired learning outcomes. The implication of this research is that teachers can formulate prevention and suppress extreme and radical views in madrasah, especially Islamic elementary schools with a strategy of strengthening religious moderation in the independent learning curriculum. Keywords: Religious Moderation; Free Learning; Islamic Religious Education.